O erro como consequência da desestabilização da vontade e do consentimento do consumidor na compra e venda consumerista - Trigueiros, Ângelo Mário Costa e (2007)
The Consumers Defense Code (law nº 8.078, from September, 11th, 1990) brought to the national legal system not only novelty, but mainly a discipline mechanism and practical tools to solve conflicts arising from consumer connections. This modest study intends to broach some important aspects from consumers purchase agreement, specially those related to the development of the volitive element of its formation and to the error as a consequence of both the will and the consumer consentment destabilization. Convinced that the agreements resulting from consumer connections so far have been studied incompletely, this study tries to demonstrate that it s composing elements, as usually described, must be developed, since the authors, apparently, mix the parties volition with their consentment. On the other hand, at the same time, this study tries to demonstrate the consentment and volitive defects must be examined under a different point of view, and, therefore, must be redefined. More specifically, this studies efforts to demonstrate that the error, understood as a defect from the consumer connection, is not a fact by itself, but a mere consequence of the consumers volition and consentment destabilization originated by a malevolent cause to his rights, interests or conveniences. Consumers rights, even though without a great chronological tradition among us, soon has distinguished itself, not only due to its practical and moralizing magnitude in the business scenario, but mainly due to its authors qualitative relevance. The emerging of mass societies forced old conceptions regarding the purchase agreement to be revised. One of those revisions was the verification that, in certain agreements, one of the parties (the consumer) is so diluted that becomes almost invisible, imperceptible. This fact heavily renders difficult to the study of consumer agreements formation, based on doctrinaire fundaments belonging exclusively to this area of the law. This is the reason why this study frequently recurred to the old civil law doctrine. This approach to the matter does not make this study ill at ease since, as is well known, consumers´ law must not be seen as a totally separated branch of the legal tree. For all this reasons this study understands to have contributed modestly and unpretentiously to the study of consumers purchase agreement and the error resulting from the destabilization of consumer s volition and consentment